FORMATION OF THE CONCEPTUAL FEATURES OF MANAGEMENT ACCOUNTING AT THE ENTERPRISE. (Journal of Economic Research & Business Administration, 2016)
Information  necessary  for  control  and comparison  of  actual  results with  planned  is  formed  in an  administrative  account,  on  structural subdivisions and segments of organization, and also for the acceptance of different administrative decisions, planning and estimation of  alternative variants of actions. For the acceptance of different operative economic decisions managers and leaders need reliable information,both about productive and about financial position of enterprise. Exactly it served principal reason of selection of administrative account as an independent element of the system of record-keeping. The problem of formation of management accounting is to reorient of the domestic theory and practice on the new challenges facing the management of the organization in the marketplace. Another object of the national management accounting is the creation and development of new and innovative systems on practice about generating information on the production cost.